Evidence of taxonomic and functional recovery of macroinvertebrate communities following river restoration - England, Judy; Hayes, Chloe; White, James C.; Johns, Tim (MDPI, 2021)
River ecosystems have been heavily degraded globally due to channel hydromorphological modifications or alterations to catchment-wide processes. Restoration actions aimed at addressing these changes and restoring ecological integrity are increasing, but evidence of the effectiveness of these actions is variable. Using a rare 7-year before-after-control-impact (BACI) study of restoration of a lowland groundwater-fed river in England, UK, we explore changes in the macroinvertebrate community following the removal of impoundments and channel narrowing to aid restoration of physical processes. Restoration activity prompted significant taxonomic and functional responses of benthic invertebrate communities in the 4 years post-restoration. Specifically, significant gains in taxonomic and functional richness were evident following restoration, although corresponding evenness and diversity measures did not mirror these trends. Restoration activities prompted a shift to more rheophilic taxa and associated traits matching the physical changes to the channel and habitat composition. Temporal changes were clearer for taxonomic compositions compared to the functional properties of macroinvertebrate communities, indicating a functional redundancy effect of new colonists inhabiting restored reaches following restoration. The results highlight the value of long-term BACI studies in river restoration assessments, as well as project appraisals incorporating both taxonomic and functional observations. We highlight the urgent need of such studies to provide evidence to inform effective river restoration strategies to address future changes such as adaption to climate change and the biodiversity crisis
Keywords: hydromorphology; connectivity; BACI; diversity; groundwater fed river